PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA KARYAWAN THE AMERICAN CLUB JAKARTA - Wiwin Wianti (Universitas Bina Sarana Informatika, 2018)
This study was conducted to determine and analyze the influence of organizational culture, compensation and organizational commitment on employee job satisfaction to The American Club Jakarta. The Method used is a survey with a causal approach. The result of the survey were analyzed by using a casual approach path analysis with software LISREL 8.70. A technique used in sampling is saturated sampling (total sampling), where all of the population is used as sample are 60 respondents. The results of this study are the direct influence of organizational culture on job satisfaction, the direct influence of compensation on job satisfaction, the direct influence of organizational commitment on job satisfaction, the direct influence organizational culture on organizational commitment, the direct influence compensation on organizational commitment. The indirect influence organizational culture on job satisfaction through the organizational commitment, the indirect influence compensation on job satisfaction through the organizational commitment. Based on these results concluded that the most dominant of direct influence on job satisfaction is compensation. While most dominant variation of organizational commitment is influenced by compensation.